Variations of Food in Traditional Muslim Ceremonies in Minangkabau Isolect, Indonesia - Nadra, Nadra (Environment-Behaviour Proceedings Journal, 2023)
This study describes the variations of food in Minangkabau’s isolect that are commonly used in traditional Muslim ceremonies. Informal discussion and observation were conducted using various techniques on selected ceremonies. Five distinct traditional Muslim ceremonies are found in this study. Furthermore, the result discovered that there are nine foods for dishes and vegetables, eleven items for snacks, three items for drinks and one item for fruit. This included the foods that were classified into one, two, and three lexicons. Overall, it may be concluded that food variations always occur in every traditional Muslim ceremony.